The Diagnosis and Management of Recurrent Ischemic Priapism, Priapism in Sickle Cell Patients, and Non-Ischemic Priapism: An AUA/SMSNA Guideline. Issue 1 (10th July 2022) - Bivalacqua, Trinity J.; Allen, Bryant K.; Brock, Gerald B.; Broderick, Gregory A.; Chou, Roger; Kohler, Tobias S.; Mulhall, John P.; Oristaglio, Jeff; Rahimi, Leila L.; Rogers, Zora R.; Terlecki, Ryan P.; Trost, Landon; et al.
Abstract : Purpose: Priapism is a persistent penile erection that continues hours beyond, or is unrelated to, sexual stimulation and results in a prolonged and uncontrolled erection. Given its time-dependent and progressive nature, priapism is a situation that both urologists and emergency medicine practitioners must be familiar with and comfortable managing. Methodology: A comprehensive search of the literature on acute ischemic priapism and non-ischemic priapism (NIP) was performed by Emergency Care Research Institute for articles published between January 1, 1960 and May 1, 2020. A search of the literature on NIP, recurrent priapism, prolonged erection following intracavernosal vasoactive medication, and priapism in patients with sickle cell disease was conducted by Pacific Northwest Evidence-based Practice Center for articles published between 1946 and February 19, 2021. Searches identified 4117 potentially relevant articles, and 3437 of these were excluded at the title or abstract level for not meeting inclusion criteria. Full texts for the remaining 680 articles were ordered, and ultimately 203 unique articles were included in the report. Results: This Guideline provides a clinical framework for the treatment (non-surgical and surgical) of NIP, recurrent ischemic priapism, and priapism in patients with sickle cell disease. The treatment of patients with a prolonged erection following intracavernosal vasoactive medication is also included. The AUA guideline on the diagnosis of priapism and the treatment of acute ischemic priapism was published in 2021. Conclusions: All patients with priapism should be evaluated emergently to identify the sub-type of priapism (acute ischemic versus non-ischemic) and those with an acute ischemic event should be provided early intervention when indicated. NIP is not an emergency and treatment must be based on patient objectives, available resources, and clinician experience. Management of recurrent ischemic priapism requires treatment of acute episodes and a focus on future prevention of an acute ischemic event. Sickle cell disease patients presenting with an acute ischemic priapism event should initially be managed with a focus on urologic relief of the erection; standard sickle cell assessment and interventions should be considered concurrent with urologic intervention. Treatment protocols for a prolonged, iatrogenic erection must be differentiated from protocols for true priapism.